PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIIE DI SMPN 2 BANGOREJO - Nuryah, Dian Fajar; Sukijo, Sukijo; Muntholib, Muntholib (Universitas Tanjungpura, 2023)
This classroom action research has a background of low students' critical thinking skills. The research objective is to improve critical thinking skills using problem-based learning models. This classroom action research was carried out according to the Kemmis and Taggart models consisting of planning, implementation, observation and reflection. The research process was carried out in two cycles where each cycle contained two lessons. Assessment of critical thinking skills is measured using description questions given at the end of each learning cycle according to the five indicators of critical thinking skills. The results of research using the problem based learning model can improve students' critical thinking skills. In cycle 1 the results were 60% in the quite good category and in the second cycle the results were 79% in the good category. Achievement of students in cycle 1 on the indicators of elementary clarification 73% (good enough), basic support 56% (poor), inference 48% (very little), advance clarification 55% (poor), strategies and tactics 67% (good enough). Achievements in cycle 2 on the indicators of elementary clarification 85% (good), basic support 81% (good), inference 74% (good), advance clarification 77% (good), strategies and tactics 67% (good). Based on research consisting of two cycles, it is known that problem based learning can improve critical thinking skills because students are trained to solve problems and obtain solutions. From these results it can be concluded that critical thinking skills can be improved by applying the problem based learning model.